Prenatal Diagnosis of Tyrosinemia Type 1 Using Next Generation Sequencing. (3rd July 2016) - Rafati, Maryam; Mohamadhashem, Faezeh; Hoseini, Azadeh; Ramandi, Somayeh Darzi; Ghaffari, Saeed Reza
ABSTRACT: Prenatal diagnosis using conventional molecular genetic techniques may be encountered with some limitations when the disease causing mutation is unknown. Here, we report on prenatal diagnosis of tyrosinemia in a family with consanguineous marriage and two affected children in whom no disease causing mutation had been identified before pregnancy. Mutation analyses of three genes associated with tyrosinemia including FAH, TAT and HPD were carried out in the fetal DNA sample using Next Generation Sequencing. A heterozygous nonsense mutation (p.Arg237Ter) in FAH gene was detected in the fetus. Further investigations suggested that the fetus was carrier of tyrosinemia type 1. This study demonstrates the successful application of Next Generation Sequencing in prenatal diagnosis, when the time is a limiting factor, more than one (especially large) responsible genes are involved, a "founder" or a "previously detected" mutation is not present and hence the conventional molecular genetic investigations cannot be employed.